Histomorphology and Physical Characteristics of Buffalo Meat at Different Sex and Age - H Nuraini; . Mahmudah; A Winarto; C Sumantri (Faculty of Animal Science, Bogor Agricultural University, 2013)
The aim of this experiment was to evaluate histology and physical variables of buffalo meat at different sex and ages. Thirty head of buffaloes were used in this experiment. Muscle fiber diameter, fasciculus diameter, thickness of connective tissue, pH, water holding capacity, Warner-Bratzler shear force and cooking loss were measured in this experiment. Analysis of variance of randomized factorial design was used to analyse the data. The differences were analysed by Tukey test. The result showed that muscle fiber diameter was influenced by ages. The difference muscle fiber diameter among ages indicated that 8-12 mo and 1.5 yr old have smaller diameter compared to three year old (P<0.05), but there was no differences between two, three and four years old. The fasciculus diameter, thickness of connective tissue, tenderness, pH value, water holding capacity, and cooking lost indicated no significant found in all stage of age and sex of samples. Meat qualities of buffaloes were not affected by age (2-4 yr) and sex.